STRATEGI PEMELIHARAAN RANPUR ANOA UNTUK MENINGKATKAN KESIAPAN OPERASIONAL SATGAS YONMEK GARUDA XXIII UNIFIL - Ari Yulianto; Ferdinand Hasudungan; Oktaheroe Ramsi (Jurnal Manajemen Bisnis Krisnadwipayana, 2025)
The maintenance of Anoa armored vehicles is crucial for the operational readiness of the TNI Konga XXIII UNIFIL Mechanized Battalion Task Force amidst the challenging terrain of South Lebanon. This descriptive qualitative study aims to analyze system effectiveness and personnel competence factors, and to formulate maintenance strategies through in-depth interviews. The findings reveal that while preventive and corrective maintenance systems function effectively, they currently lack digital integration. Technician competence is significantly influenced by pre-deployment training and field experience. Consequently, effective strategies are formulated through strengthened coordination with PT Pindad, the implementation of an Integrated Maintenance Support System (IMSS), and the establishment of a forward maintenance hub. The study concludes that collaborative, adaptive, and digital technology-based strategies are essential for maintaining operational readiness. Strengthening digitalization and technician competence is recommended to support the modernization of TNI defense logistics.